1951
DOI: 10.1111/j.1360-0443.1951.tb04909.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the 1949/1950 Literature of Addiction

Abstract: THIS review provides an integrated bibliography and digest of all aspects of alcoholism and drug addiction, including a section on tobacco. It is the third review to appear in the JOURNAL, and covers the world literature on addiction published from the middle of 1949 t o the end of 1950. Well over a hundred articles on Antabuse have appeared during this period, and we have attempted to provide a comprehensive bibliography of this drug.To facilitate orientation and reference, this review is headed by a synopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1958
1958
1975
1975

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However these techniques require experimental validation. Should a direct relationship be demonstrated between laboratory conditioning and responses to conditioned aversion therapy using (say) apomorphine it would seriously weaken the arguments of those who assume (118,142) that the effectiveness of these aversion techniques is in no way based upon conditioning. It may be observed that a similar exposition might be developed for the prediction of success in any form of psychotherapy.…”
Section: Predicting Success In Conditioned Aversion Therapymentioning
confidence: 99%
“…However these techniques require experimental validation. Should a direct relationship be demonstrated between laboratory conditioning and responses to conditioned aversion therapy using (say) apomorphine it would seriously weaken the arguments of those who assume (118,142) that the effectiveness of these aversion techniques is in no way based upon conditioning. It may be observed that a similar exposition might be developed for the prediction of success in any form of psychotherapy.…”
Section: Predicting Success In Conditioned Aversion Therapymentioning
confidence: 99%